An interval global optimization algorithm for a class of functions with several variables - Mohd, Ismail (Elsevier Science Publishers, 1990)
In this paper some of the ideas which have been used in an algorithm for computing and bounding the global minimizers of a twice continuously differentiable function with several variables in a given compact interval vector using interval arithmetic are described.